2005
DOI: 10.1039/b504698j
|View full text |Cite
|
Sign up to set email alerts
|

Development of a high ratio isotope dilution mass spectrometry calibration technique for chemical metrology

Abstract: IDMS with calibration by ''exact'' or ''approximate signal matching'' methods offers a number of advantages for chemical metrology applications where measurements of low uncertainty are required for analytes at low concentrations in complex matrices. These methods have been applied extensively but are unsuitable for some important applications because in many cases, the concentration of the spike isotope in each measured blend of a sample or standard should be as close as possible to the concentration of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…[6,7] Today, IDMS is the only accepted method to realize SI-traceable amount-of-substance measurements, and, thus, most national metrology institutes (NMIs) have built their national standards in analytical chemistry upon this technique. [8,9] From a metrological point of view, it is therefore desirable to have an alternative approach, which is based on a different physical principle. Tackling analytical problems with different measurement techniques allows the identification of hidden contributions to the measurement uncertainty and might generally improve the reliability of a comparison.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Today, IDMS is the only accepted method to realize SI-traceable amount-of-substance measurements, and, thus, most national metrology institutes (NMIs) have built their national standards in analytical chemistry upon this technique. [8,9] From a metrological point of view, it is therefore desirable to have an alternative approach, which is based on a different physical principle. Tackling analytical problems with different measurement techniques allows the identification of hidden contributions to the measurement uncertainty and might generally improve the reliability of a comparison.…”
Section: Introductionmentioning
confidence: 99%
“…The isotopic ratios attained in this way for coral samples were: 24 Mg ⁄ 25 Mg $ 0.4, 48 Ca ⁄ 43 Ca $ 0.12 and 88 Sr ⁄ 87 Sr $ 1.2, close to the optimal ratios predicted by isotope dilution error equations of 0.34, 0.04 and 1 respectively. In the case of Ca, a ratio three times larger was used in order to minimise the use of this costly isotope, although this does not entail a significant deterioration of the method precision (Hearn et al 2005). Solutions were aspirated in aliquots of about 50 ll (for the lowest flow rate nebuliser), at least three times during the analysis sequence.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, inductively coupled plasma mass spectrometry (ICP‐MS) has been investigated as a means of measuring the sulfur amount of lower concentration materials . The main advantage of ICP‐MS techniques over ID‐TIMS is the elimination of the chemical reduction procedure needed for the latter technique.…”
Section: Isobaric Inteferences On the Sulfur Isotope Massesmentioning
confidence: 99%
“…ICP‐MS techniques generally require less sample processing and consequently are relatively free of chemical processing blank contributions. The use of ID‐ICP‐MS, whether employing a quadrupole ICP‐MS or a sector‐field instrument, has shown that lower blanks are achievable . However, corrections for instrumental and matrix‐induced mass bias are larger and more variable than those observed for TIMS.…”
Section: Isobaric Inteferences On the Sulfur Isotope Massesmentioning
confidence: 99%
See 1 more Smart Citation